2014
DOI: 10.1590/s0100-83582014000100017
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate influence on the physiological parameters of Conyza bonariensis biotypes

Abstract: -The objective of this study was to determine changes in gas exchange and inhibition of EPSPs, based on the accumulation of shikimic acid in horseweed biotypes resistant and sensitive to glyphosate. Two experiments were conducted in a factorial model. The first one evaluated horseweed biotypes (one resistant and one susceptible to glyphosate), and herbicide rates (0 and 1,080 g a.e. ha 1 ) applied on the weed. In the second experiment, the horseweed biotypes (susceptible and resistant to glyphosate) were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
1
6
0
1
Order By: Relevance
“…Both R and S C. bonariensis biotypes accumulated shikimic acid (i.e., glyphosate was equally loaded in the phloem and reached the EPSPS in both biotypes) [29]. Similar results have been found in different studies where both R and S biotypes/populations of Conyza species accumulated shikimic acid [4,30,31]; however, the accumulation rates of shikimic acid in R plants was always lower than the accumulation observed in S plants. The low accumulation of shikimic acid between our R C. bonariensis biotypes suggests different resistance mechanism(s), which reduced the amount of glyphosate that reached or interacted with the EPSPS [27].…”
Section: Discussionsupporting
confidence: 84%
“…Both R and S C. bonariensis biotypes accumulated shikimic acid (i.e., glyphosate was equally loaded in the phloem and reached the EPSPS in both biotypes) [29]. Similar results have been found in different studies where both R and S biotypes/populations of Conyza species accumulated shikimic acid [4,30,31]; however, the accumulation rates of shikimic acid in R plants was always lower than the accumulation observed in S plants. The low accumulation of shikimic acid between our R C. bonariensis biotypes suggests different resistance mechanism(s), which reduced the amount of glyphosate that reached or interacted with the EPSPS [27].…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, the resistant population, although showing negative values at 3 DAA, at 7 DAA recovered. Vargas et al (2014) have not found differences in water-use efficiency (WUE) at 3 DAA of glyphosate between the biotypes of horseweed susceptible and resistant to it. However, at 7 DAA there was a large difference.…”
Section: Cs Cr Cs Cr Cs Crmentioning
confidence: 82%
“…Several studies have been carried out to understand the plants physiology after the application of herbicides (Zobiole et al, 2010a;Orcaray et al, 2012;Yanniccari et al, 2012a, b;Vargas et al, 2014). Physiological knowledge about weeds -in this case, ryegrass is important for an efficient management, as it may help in understanding glyphosate resistance mechanisms, as well as the intensity of effects on susceptible and resistant biotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the most notorious are Conyza canadensis (L.) Cronq., Conyza bonariensis (L.) Cronq., and Conyza sumatrensis (Retz.) E. Walker [1], which are known as major invaders in different crops across continents [2] [3].…”
Section: Introductionmentioning
confidence: 99%